Galactopyranoside-Substituted N‑Heterocyclic Carbene Gold(I) Complexes: Synthesis, Stability, and Catalytic Applications to Alkyne Hydration - Hobsteter, Ariana Wanda (2022)
A series of novel gold(I) complexes bearing galactopyranoside-based N-heterocyclic carbene ligands have been synthesized via transmetalation of the corresponding Ag(I) complex. Gold(I) complexes have been characterized by NMR, Fourier transform infrared (FTIR), and elemental analysis. An exhaustive NMR analysis shows that the complexes are not stable when hydroxyl groups are deprotected. Catalytic studies, using the alkyne hydration as a model reaction, indicate that the synthesized complexes are active and reusable.